The Relationship of Knowledge Management to Human Resources Development of Viriyah Insurance Public Company Limited in Thailand 4.0 - Suksomrit, Suwat; Piemmetta, Jakpong (Arts of Management Journal, 2018)
This research aims to study the current knowledge management and the relationship between knowledge management and information technology for staff competency. Viriyah Insurance PLC., in the age of Thailand 4.0. This is a qualitative research using structured questionnaires that were proved by three experts and found to be consistent with the objectives. The key informants were 25 employees from the company. The data was analyzed and described descriptively. The study found that knowledge management in the present time, most employees are always alert and self-motivated, but there are limitations on the rational factor. The differences and the relationship between knowledge management and information technology for employee performance of this company are necessary in order to keep up with changes. Also to be in the insurance industry, it's important to adapt to the relationship of knowledge management with information technology.